Phenolic-Rich Plant Extracts With Antimicrobial Activity: An Alternative to Food Preservatives and Biocides? - Oulahal, Nadia; Degraeve, Pascal (Frontiers in Microbiology, 2022)
In recents years, the search for natural plant-based antimicrobial compounds as alternatives to some synthetic food preservatives or biocides has been stimulated by sanitary, environmental, regulatory, and marketing concerns. In this context, besides their established antioxidant activity, the antimicrobial activity of many plant phenolics deserved increased attention. Indeed, industries processing agricultural plants generate considerable quantities of phenolic-rich products and by-products, which could be valuable natural sources of natural antimicrobial molecules. Plant extracts containing volatile (e.g. essential oils) and non-volatile antimicrobial molecules can be distinguished. Plant essential oils are outside the scope of this review. This review will thus provide an overview of current knowledge regarding the promises and the limits of phenolic-rich plant extracts for food preservation and biofilm control on food-contacting surfaces. After a presentation of the major groups of antimicrobial plant phenolics, of their antimicrobial activity spectrum, and of the diversity of their mechanisms of action, and their most promising sources will be reviewed. Since antimicrobial activity reduction often observed when comparing in vitro and in situ activities of plant phenolics has often been reported as a limit for their application, the effects of the composition and the microstructure of the matrices in which unwanted microorganisms are present (e. g. food and/or microbial biofilms) on their activity will be discussed. Then, the different strategies of delivery of antimicrobial phenolics to promote their activity in such matrices, such as their encapsulation or their association with edible coatings or food packaging materials are presented. The possibilities offered by encapsulation or association with polymers of packaging materials or coatings to increase the stability and ease of use of plant phenolics before their application, as well as to get systems for their controlled release are presented and discussed. Finally, the necessity to consider phenolic-rich antimicrobial plant extracts in combination with other factors consistently with hurdle technology principles will be discussed. For instance, several authors recently suggested that natural phenolic-rich extracts could not only extend the shelf-life of foods by controlling bacterial contamination, but could also co-exist with probiotic lactic acid bacteria in food systems to provide enhanced health benefits to human.